Measuring aspirations: Discussion and example from Ethiopia - Bernard, Tanguy; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2012)
Individuals’ aspirations and their consequences for future-oriented behavior have received increased attention in devel-opment economics literature in recent years. At this stage, however, each study relies on ad hoc empirical instruments to measure aspirations, thereby limiting comparability of the results obtained. This paper proposes a simple measurement instrument that spans several dimensions aggregated via individual-specific weights. We use a purposefully collected data set to test for the usability, reliability, and validity of the instrument. In addition to standard test-retest procedures, our innovation lies in the use of several randomized tests introduced within the questionnaires themselves, in the enumerators’ qualifications, and in the information set available to respondents. Overall results show strong support for the proposed instrument, with the caveat that collection of such attitudinal data requires experienced enumerators capable of adequately probing respondents.